High levels of toxigenic Clostridioides difficile contamination of hospital environments: a hidden threat in hospital-acquired infections in Kenya. Issue 12 (18th December 2020) - Odoyo, Erick; Kyanya, Cecilia; Mutai, Winnie; Musila, Lillian
Abstract : Introduction. The contribution of Clostridioides difficile (formerly Clostridium difficile ) to the burden of hospital-associated infections (HAIs) remains undetermined in many African countries. Aim. This study aimed to identify a sensitive and readily adaptable C. difficile detection assay and to evaluate the C. difficile HAI risk in Kenya. Methodology. Sterile swabs in neutralizing buffer were used to sample equipment or surfaces that patients and clinical staff touched frequently. These swabs were either plated directly on chromogenic agar or cultured in an enrichment broth before plating. The swab suspensions, enrichment broth and plate cultures were screened by quantitative PCR (qPCR) to determine the most efficient detection method. The HAI risk was evaluated by testing the C. difficile -positive samples by qPCR for the A, B and binary toxins. Results. C. difficile was detected on 4/57 (7.0 %) equipment and surfaces by direct culture. The additional enrichment step increased the detection rate 10-fold to 43/57 (75.4 %). In total, 51/57 (89.5 %) environmental samples were positive for C. difficile detected through either culture or qPCR. The genes encoding the primary toxins, tcdA and tcdB, were detected on six surfaces, while the genes encoding the binary toxins, cdtA and cdtB, were detected on 2/57 (3.5 %) and 3/57 (5.3 %) surfaces, respectively. Different C. difficile toxin gene profiles were detected: the tcdA+/tcdB − gene profile on 4/10 (40 %) high-touch surfaces, tcdA−/tcdB + on 3/10 (30 %) surfaces, tcdA+/tcdB+/cdtA+/cdtB+ on 2/10 (20 %) surfaces and tcdA−/tcdB+/cdtB+ on one high-touch surface. Conclusion. The widespread contamination of hospital environments by toxigenic C. difficile gives a strong indication of the high risk of C. difficile infections (CDIs). The two-step culture process described can easily be adapted for monitoring hospital environment contamination by C. difficile .